South American Hemorrhagic Fevers: A summary for clinicians. (April 2021) - Frank, Maria G.; Beitscher, Adam; Webb, Camille M.; Raabe, Vanessa; Beitscher, Adam; Bhadelia, Nahid; Cieslak, Theodore J.; Davey, Richard T.; Dierberg, Kerry; Evans, Jared D.; Frank, Maria G.; et al.
Highlights: South American Hemorrhagic Fevers are caused by 5 Mammarenaviruses. Infection occurs from contact with infected persons, rodents, or their environment. The nonspecific initial symptoms resemble influenza without respiratory symptoms. Diagnosis of viral hemorrhagic fevers requires a skillfully obtained travel history. Two treatments and one vaccine are potential SAHF medical countermeasures. Abstract: Objectives: This article is one of a series on acute, severe diseases of humans caused by emerging viruses for which there are no or limited licensed medical countermeasures. We approached this summary on South American Hemorrhagic Fevers (SAHF) from a clinical perspective that focuses on pathogenesis, clinical features, and diagnostics with an emphasis on therapies and vaccines that have demonstrated potential for use in an emergency situation through their evaluation in nonhuman primates (NHPs) and/or in humans. Methods: A standardized literature review was conducted on the clinical, pathological, vaccine, and treatment factors for SAHF as a group and for each individual virus/disease. Results: We identified 2 treatments and 1 vaccine platform that have demonstrated potential benefit for treating or preventing infection in humans and 4 other potential treatments currently under investigation. Conclusion: We provide succinct summaries of these countermeasures to give the busy clinician a head start in reviewing the literature if faced with a patient with South American Hemorrhagic Fever. We also provide links to other authoritative sources of information.